A Software Ability Link for Service-Oriented Architectures (Global Journal of Management and Business Research, 2014)
Business intelligence is employed to explain applications and technologies that area unit wont to gather, offer access to and analyze knowledge and data regarding the organization, to assist Create higher business choices. A Business Intelligence Networks area unit 2 thing: first, Associate in Nursing rising conception for the agile composition of e-business worth chains, and second a brand new stream of analysis. whereas there a coherent vision of Business Intelligence Networks and therefore the associated practicality, there's meager understanding of why making and maintaining such infrastructure and networks is as tough as being knowledgeable about in real-world situations. during this work trace back the quality of partner choice, method composition, and execution watching to the shortage of linguistics within the description of system components in Intelligence Networks surroundings, and its propose a service-oriented design as a the foundational layer for future Business Networks, and show however our approach considerably reduces the quality of the core network management tasks by lifting them to the next level of abstraction.
Keywords: service-oriented architecture; business intelligence; semantic layered architecture